Lipid indices as simple and clinically useful surrogate markers for insulin resistance in the U.S. population - Lee, Juncheol; Kim, Bongyoung; Kim, Wonhee; Ahn, Chiwon; Choi, Hyun Young; Kim, Jae Guk; Kim, Jihoon; Shin, Hyungoo; Kang, Jun Goo; Moon, Shinje (Scientific reports, 2021)
This study aimed to compare the accuracy of novel lipid indices, including the visceral adiposity index (VAI), lipid accumulation product (LAP), triglycerides and glucose (TyG) index, TyG-body mass index (TyG-BMI), and TyG-waist circumference (TyG-WC), in identifying insulin resistance and establish valid cutoff values. This cross-sectional study used the data of 11,378 adults, derived from the United States National Health and Nutrition Examination Survey (1999–2016). Insulin resistance was defined as a homeostasis model assessment-insulin resistance value above the 75th percentile for each sex and race/ethnicities. The area under the curves (AUCs) were as follows: VAI, 0.735; LAP, 0.796; TyG index, 0.723; TyG-BMI, 0.823, and; TyG-WC, 0.822. The AUCs for TyG-BMI and TyG-WC were significantly higher than those for VAI, LAP, and TyG index (vs. TyG-BMI, p < 0.001; vs. TyG-WC, p < 0.001). The cutoff values were as follows: VAI: men 1.65, women 1.65; LAP: men 42.5, women 42.5; TyG index: men 4.665, women 4.575; TyG-BMI: men 135.5, women 135.5; and TyG-WC: men 461.5, women 440.5. Given that lipid indices can be easily calculated with routine laboratory tests, these values may be useful markers for insulin resistance risk assessments in clinical settings.